Structural studies and SH3 domain binding properties of a human antiviral salivary proline‐rich peptide. Issue 5 (September 2016) - Righino, Benedetta; Pirolli, Davide; Radicioni, Giorgia; Marzano, Valeria; Longhi, Renato; Arcovito, Alessandro; Sanna, Maria Teresa; De Rosa, Maria Cristina; Paoluzi, Serena; Cesareni, Gianni; Messana, Irene; Castagnola, Massimo; et al.
Abstract: Human saliva contains hundreds of small proline‐rich peptides originated by the proteolytic cleavage of the salivary basic Proline‐Rich Proteins. Nevertheless only for few of them a specific biological activity has been assigned to date. Among them, the 1932 Da peptide (p1932) has been patented as an anti‐HIV agent. In order to shed light on the possible mechanism of action of this peptide, we assessed in this study, by means of molecular dynamics calculations, circular dichroism and FTIR spectroscopic techniques, that p1932 has an intrinsic propensity to adopt a polyproline‐II helix arrangement. This structural feature combined with the presence of PxxP motifs in its primary structure, represents an essential property for the exploitation of several biological activities. Next to these findings, we recently demonstrated the ability of this peptide to be internalized within cells of the oral mucosa, thus we focused onto a possible intracellular target, represented by the SH3 domains family. Its ability to interact with selected SH3 domains was finally assayed by Surface Plasmon Resonance spectroscopy. As a result, only Fyn, Hck, and c‐Src SH3 domains gave positive results in terms of interaction, showing dissociation constants ranging from nanomolar to micromolar values having the best performer a K D of 148 n M . It is noteworthy that all the interacting domains belong to the Src kinases family, suggesting a role for p1932 as a modulator of the signal transduction pathways mediated by these kinases. © 2016 Wiley Periodicals, Inc. Biopolymers (Pept Sci) 106: 714–725, 2016.